2017
DOI: 10.1053/j.ajkd.2016.10.027
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3-Positive Regulatory T Cells and Kidney Allograft Tolerance

Abstract: Normal immune homeostasis is achieved by several mechanisms, and prominent among them is immunoregulation. While several types of regulatory lymphocyte populations have been described, CD4 T cells expressing the Foxp3 transcription factor (Foxp3+ Tregs) are the best understood. This population of cells is critical for maintaining self-tolerance throughout the life of the organism. Foxp3+ Tregs can develop within the thymus, but also, under selected circumstances, naïve peripheral T cells can be induced to expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Small-animal studies, using strategies of target cell depletion or adoptive transfer, have demonstrated that these cells downregulate effector T-cell responses, prevent transplant arteriopathy, and contribute to allograft tolerance. 58 Of note, recent data support the hypothesis that specific induction of Tregs by donor antigens plays a key role in tolerance induced by transient mixed chimerism in non-human primate recipients of kidney, lung and heart allografts (see later). 9 …”
Section: Immune Response To An Allograft: Discoveries With Clinical Imentioning
confidence: 82%
See 2 more Smart Citations
“…Small-animal studies, using strategies of target cell depletion or adoptive transfer, have demonstrated that these cells downregulate effector T-cell responses, prevent transplant arteriopathy, and contribute to allograft tolerance. 58 Of note, recent data support the hypothesis that specific induction of Tregs by donor antigens plays a key role in tolerance induced by transient mixed chimerism in non-human primate recipients of kidney, lung and heart allografts (see later). 9 …”
Section: Immune Response To An Allograft: Discoveries With Clinical Imentioning
confidence: 82%
“…3,4 Importantly, for transplantation, the potential for these cells to contribute to clinical immunosuppression minimization and/or tolerance induction has also now been recognized. 5 …”
Section: Immune Response To An Allograft: Discoveries With Clinical Imentioning
confidence: 99%
See 1 more Smart Citation
“…42 FOXP3 regulatory cells are commonly identified in allograft tolerance. 3 In a murine model of spontaneous allograft acceptance, depletion of FOXP 3 T cells causes acute rejection of renal allografts. 41 In humans with immunosuppression, renal allograft intragraft FOXP3 T cells predicted favorable outcomes in subjects with subclinical/borderline rejections.…”
Section: | Discussionmentioning
confidence: 99%
“…Preclinical studies in the cynomolgus nonhuman primate (NHP) 1 using bone marrow transplantation (BMT) to induce mixed chimerism has led to promising phase 1 trials. 2 The immunologic mechanisms leading to peripheral tolerance are complex and likely involve, in part, regulatory T cells 3,4 and regulatory B cells. 5 Reliable identification of tolerance could benefit clinical trials and provide insights into the immunologic mechanisms.…”
Section: | Introductionmentioning
confidence: 99%